Developing Arts Loving Readers: Top Ten Questions Teachers are Asking about Integrated Arts Education - McDonald, Nan; Fisher, Douglas (Rowman & Littlefield Publishers, 2002)
Developing Arts Loving Readers is based on the premise that children can and do learn a great deal about the arts and their own abilities innately. Involvement and immersion author Nan. L. McDonald argues, are the ways in which children may feel welcome to write, move, create, draw, and otherwise express ideas about art and music directly. Teaching suggestions are offered to classroom teachers and other non-specialists, so that classroom-reading activities may be extended into group discussions, co-operative learning-arts projects, and creative performances. Appended are extensive resource lists for further integrated arts teaching in the classroom.